Psychiatric sequelae of traumatic brain injury (TBI) - Ambarish Ghosh; Birva Desai; Arghya Halder; Aniruddha Ghosh; Priyanka Das; Daniel Saldanha (Asian Journal of Medical Sciences, 2020)
Background: Traumatic brain injury (TBI), a leading cause of morbidity and mortality worldwide, is an alteration in brain function, caused by an external force. With rapid surge in urbanization, motorization and economic liberalization in India, risk of TBI is increased, raising a cause for concern about its neurological as well as psychiatric sequelae.